THE ROLE OF DIGITAL MARKETING TO CREATE COMPETITIVE ADVANTAGE TO IMPROVE MICRO BUSINESS PERFORMANCE - Diah Novianti,; Ghisya Siti Rochmah,; Siska Ernawati Fatimah, (International Journal of Innovative Technologies in Social Science, 2024)
UMKM has an important role to play in creating jobs and driving innovation. However, UMKM still faces the challenge of understanding the everexpanding information technology. The government has issued regulations to protect UMKM, but they still need enhanced capabilities in digital marketing. Entrepreneurs need to leverage digital technology and social media to create a competitive edge through design, production, marketing, delivery, and sales support. The research aims to understand the role of digital marketing in creating a competitive advantage for improving the performance of microenterprises in Indonesia, in West Java. This research uses quantitative methods. The population used in this study is the entire buyer of the culinary UMKM in the City of Cirebon. The number of samples taken using the formula Lemeshow obtained the calculation of 250 respondents. Sampling technique using incidental sampling. Data analysis technique using Structural Equation Modeling-Partial Least Square (SEM-PLS). Research results show that competitive advantage is partially influenced by marketing performance of 43% and digital marketing of 30%. This is due to the importance of the role of Digital Marketing in improving UMKM performance and creating Competitive Advantage.